Impact of the partial replacement of fish meal with a chloroplast rich fraction on the growth and selected nutrient profile of zebrafish (Danio rerio). Issue 2 (22nd January 2019) - Gedi, Mohamed A.; Magee, Kieran J.; Darwish, Randa; Eakpetch, Patchaniya; Young, Iain; Gray, David A.
Abstract : Increasing global aquaculture production, is putting pressure on fishmeal and fish oil supply. There is therefore a growing search for more sustainable sources of proteins and polyunsaturated fatty acids as fish feed ingredients. Abstract : Increasing global aquaculture production, is putting pressure on fishmeal and fish oil supply. There is therefore a growing search for more sustainable sources of proteins and polyunsaturated fatty acids as fish feed ingredients. Chloroplasts are the organelles in the leaves of plants where many of the valuable nutrients, fatty acids (FAs), amino acids, vitamins and pigments, are synthesised. Chloroplasts could be incorporated into fish diets either retained in, or liberated from, plant cells. In this study zebrafish were fed with seven different diets individually; fish were fed with diets reducing fishmeal levels (10, 20 or 50%) using either spinach leaf powder (SLP) or a chloroplast rich fraction (CRF) prepared by an established method to recover chloroplasts. Both SLP and CRF had a positive impact on the growth, taste response, whole fish FA composition, and carotenoid profile. Fish fed with CRF diets showed significantly ( P ≤ 0.05) greater α-linolenic (C18:3 n-3) and hexadecatrienoic (C16:3) acid contents than those of SLP and the control. Hexadecanoic acid (C16:3) is a unique FA in the galactolipids of the chloroplast; its presence in zebrafish tissues proves that zebrafish digest and absorb chloroplast galactolipids. The lutein profile of eggs produced by zebrafish fed with the CRF diet was significantly ( P ≤ 0.05) higher than those of SLP and the control. Alterations in egg colour were also noted, warranting further investigations of the diet impact on fish fecundity, embryo fertility, hatch rate and larval survival.